Ghana Decentralization and Agricultural Services Household Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2021)
This data is from a study conducted with 960 Ghanaian households to gather citizen perspectives on decentralization in general and specifically on the impacts of Ghana’s devolution of agricultural services, which began in 2012. The survey is split into 9 survey modules: 1. Sampling (SA) – location information about the region, district, and community where the respondent is based 2. General Information (ID) – basic demographic, educational, household background, and occupational information of respondent 3. Farming & Livestock (FL) – details about household’s farming and livestock activities 4. Agricultural Extension Services (EX) – details about access to, and use of, agriculture or livestock advisory services for the subset of the sample that has agricultural land or has their primary or secondary occupation in agriculture 5. Political and Community Participation (PP) – information about respondent’s degree of participation in collective action and voting, engagement with elected officials, and frequency of access to the news 6. Perspectives on Local Government and Decentralization (LG) - subjective views about how well local government is functioning and preferences for investment in respondent’s community 7. Household Welfare (HW) – questions about the range of assets owned by the respondent’s household, as well as access to major services (e.g. water, electricity, etc.) 8. Access to facilities (AF) – degree of household’s access to public services and facilities, such as health post, market, etc. 9. Final (FI) – enumerator observations